New approaches to resistance in Brazil and Mexico - Gledhill, John; Schell, Patience A. (Patience Alexandra), 1970- (Duke University Press, 2012)
This edited collection by scholars of both history and anthropology re-examines the concepts of resistance and the effect of neoliberalism from the 1980s to the present day comparing Brazil and Mexico, two of the largest countries in Latin America.